A clinicobacteriological study of dacryocystitis in children - Sundari, S. Shanmuga; Kontraiandi, C. (International Journal of Contemporary Pediatrics, 2020)
Background: Congenital Dacryocystitis occurs due to the congenital blockage of the nasolacrimal duct, which results from incomplete canalization of the nasolacrimal duct. It is a significant cause of ocular morbidity in children. When not treated early, complications such as recurrent conjunctivitis, acute on chronic dacryocystitis, lacrimal abscess and fistula formation can occur. It is also a threat to the integrity of the eye by becoming the source of infection to orbital cellulitis and panophthalmitis. In the era of antibiotic resistance, the microbiological workup of congenital dacryocystitis is very useful for subsequent treatment. Aim of the study was to determine the microbial profile of congenital dacryocystitis and the appropriate antimicrobial agents based on the sensitivity pattern of the isolated microorganisms. Methods: A total of 25 clinically diagnosed cases of dacryocystitis in children less than 5 years of age attending the outpatient department were included in the study. Samples were collected from these patients and processed by standard microbiological techniques. All the bacterial isolates obtained were subjected to antimicrobial susceptibility testing by using Kirby-Bauer disc diffusion method. Results: Culture positivity was noted as 56% in this study. It is observed that Gram-positive bacteria were the predominant isolates of 86%. The predominant organism isolated was Streptococcus pneumoniae 43%, followed by Staphylococcus aureus 29%, Staphylococcus epidermidis 14% and Pseudomonas aeruginosa 14%. All Gram-positive organisms were highly sensitive to Gatifloxacin and least sensitive to Ciprofloxacin. All Gram-negative organisms were highly sensitive to Tobramycin and least sensitive to Ciprofloxacin and Gentamicin. Conclusions: Streptococcus pneumoniae was the common pathogen in congenital dacryocystitis. Gatifloxacin and Tobramycin are the most effective drugs. Microbial culture and sensitivity should be performed in all dacryocystitis cases. This would contribute to the choice of appropriate and effective antimicrobial agents.